LC-UV and LC-MS evaluation of stress degradation behaviour of tenatoprazole - Mahadik, Mahadeo V.; Bhusari, Vidhya K.; Kulkarni, Mahesh J.; Dhaneshwar, Sunil R. (Journal of Pharmaceutical and Biomedical Analysis, 2009)
In the present study, comprehensive stress testing of tenatoprazole was carried out according to ICH guideline Q1A (R2). Tenatoprazole was subjected to stress conditions of hydrolysis, oxidation, photolysis and neutral decomposition. Additionally, the solid drug was subjected to 50 degrees C for 60 days in dry-bath, and to the combined effect of temperature and humidity at 40 degrees C/75% RH. Extensive degradation was found to occur in acidic, neutral and oxidative conditions. Mild degradation was observed in basic conditions. The drug is relatively stable in the solid-state. The products formed under different stress conditions were investigated by LC and LC-MS. Successful separation of drug from degradation products formed under stress conditions was achieved on a Chemito ODS-3 column [C(18) (5 mu m, 250 mm x 4.6 mm, i.d.)] using methanol: 0.01 M acetate buffer pH 4.5 adjusted with glacial acetic acid (55:45) as the mobile phase at flow rate of 1 mL/min and the peak was detected using a UV detector set at 306 nm. The LC-MS m/z values and fragmentation patterns of degradation products formed under different stress conditions were studied and characterized through LC-MS fragmentation. Based on the results, degradation pathway for drug has been proposed. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: HPLC; Stability-indicating method; Stress studies; Tenatoprazole; Validation

Low plasma albumin levels are associated with increased plasma protein glycation and HbA1c in diabetes - Bhonsle, Hemangi S.; Korwar, Arvind M.; Kote, Sachin S.; Golegaonkar, Sandeep B.; Chougale, Ashok D.; Shaik, Mahemud L.; Dhande, Nitin L.; Giri, Ashok P.; Shelgikar, Kishore M.; Boppana, Ramanamurthy; Kulkarni, Mahesh J. (Journal of Proteome Research, 2012)
Albumin is one of the most abundant plasma proteins and is heavily glycated in diabetes. In this study, we have addressed whether variation in the albumin levels influence glycation of plasma proteins and HbA1c. The study was performed in three systems: (1) streptozotocin (STZ)-induced diabetic mice plasma, (2) diabetic clinical plasma, and (3) in vitro glycated plasma. Diabetic mice and clinical plasma samples were categorized as diabetic high albumin plasma (DHAP) and diabetic low albumin plasma (DLAP) on the basis of their albumin levels. For the in vitro experiment, two albumin levels, high albumin plasma (HAP) and low albumin plasma (LAP), were created by differential depletion of plasma albumin. Protein glycation was studied by using a combination of two-dimensional electrophoresis (2DE), Western blotting, and LC-MSE. In both mice and clinical experiments, an increased plasma protein glycation was observed in DLAP than in DHAP. Additionally, plasma albumin levels were negatively correlated with HbA1c. The in vitro experiment with differential depletion of albumin mechanistically showed that the low albumin levels are associated with increased plasma protein glycation and that albumin competes for glycation with other plasma proteins.
Keywords: advanced glycation end products (AGEs); Albumin; glucose; post translational modification

Limonene inhibits Candida albicans growth by inducing apoptosis - Thakre, Archana; Zore, Gajanan; Kodgire, Santosh; Kazi, Rubina; Mulange, Shradha; Patil, Rajendra; Shelar, Amruta; Santhakumari, Bayitigeri; Kulkarni, Mahesh J.; Kharat, Kiran; Karuppayil, Sankunny Mohan (Medical Mycology, 2018)
Anti-Candida potential of limonene was evaluated against planktonic growth, biofilm (adhesion, development and maturation) and morphogenesis of Candida albicans in this study. Limonene is a major constituent of citrus oil and most frequently used terpene in food and beverage industry due to its pleasant fragrance, nontoxic, and is generally recognized as safe (GRAS) flavoring agent as well as treatment option in many gastrointestinal diseases. Limonene exhibited excellent anti-Candida activity and was equally effective against planktonic growth of C. albicans isolates differentially susceptible to FLC (N = 35). Limonene inhibited morphogenesis significantly at low concentration. However, it showed stage dependent activity against biofilm formation, that is, it was more effective against adhesion followed by development and maturation. Limonene also exhibited excellent synergy with FLC against planktonic and biofilm growth. SWATH-MS analysis led to identification of limonene responsive proteins that provided molecular insight of its anti-Candida activity. Proteomic analysis revealed upregulation of proteins involved in cell wall glucan synthesis (Kre6); oxidative stress (Rhr2, Adh7 and Ebp1); DNA damage stress (Mbf1 and Npl3); nucleolar stress (Rpl11, Rpl7, Rpl29, Rpl15) and down regulation of cytoskeleton organization (Crn1, Pin3, Cct8, Rbl2), and so forth, in response to limonene. Limonene mediated down regulation of Tps3 indicates activation of caspase (CaMca1) and induction of apoptosis in C. albicans. These results suggest that limonene inhibits C. albicans growth by cell wall/membrane damage induced oxidative stress that leads to DNA damage resulting into modulation of cell cycle and induction of apoptosis through nucleolar stress and metacaspase dependent pathway.